Pulsed-Field Gel Electrophoresis of Multidrug-Resistant and -Sensitive Strains of Pseudomonas aeruginosa from a Malaysian Hospital - Thong, Kwai Lin; Lai, Kin Seng; Ganeswrie, R.; Puthucheary, S.D. (Institute of Infectious Diseases, 2004)
Over a period of 6 months from January to June 2002, an unusual increase in the isolation of highly resistant Pseudomonas aeruginosa strains was observed in the various wards and intensive care units of a large general hospital in Johor Bahru, Malaysia. An equal number of multidrug-resistant (MDR) and drug-susceptible strains were collected randomly from swabs, respiratory specimens, urine, blood, cerebral spinal fluid, and central venous catheters to determine the clonality and genetic variation of the strains. Macrorestriction analysis by pulsed-field gel electrophoresis showed that the 19 MDR strains were genetically very homogenous; the majority showed the dominant profile S1 (n = 10), the rest very closely related profiles S1a (n = 1), S2 (n = 4), and S2a (n = 3), indicating the endemicity of these strains. In contrast, the 19 drug-sensitive strains isolated during the same time period were genetically more diverse, showing 17 pulsed-field profiles (F = 0.50 - 1.00), and probably derived from the patients themselves. The presence of the MDR clone poses serious therapeutic problems as it may become endemic in the hospital and give rise to future clonal outbreaks. There is also the potential for wider geographical spread.